Institutional Ethnography, Adult Education and Program Planning: A Contribution to Critical Research - Shivaani A. Selvaraj (Adult Education Research Conference, 2014)
Many adult educators approach education as a vehicle for social change in a politically contested environment. In this paper, I introduce institutional ethnography’s analytic contribution to critical research in program planning, particularly in expanding our understanding of the mechanisms of power that operate in educational programs.